Impact of anti-mycotic drugs on the osteogenic response of bone marrow mesenchymal stem cells in vitro - Bewersdorf, Tim; Hofmann, Jakob; Findeisen, Sebastian; Schamberger, Christian T.; Lingner, Thomas; Sommer, Ulrike; Schmidmaier, Gerhard; Großner, Tobias (Antibiotics, 2024)
The treatment of fungal bone infections and infected non-unions is a huge challenge in modern trauma and orthopedics, which normally contain the local and systemic administration of anti-fungal drugs. Although frequently used, little is known about the impact of systemic and locally administered fungicides on the osteogenic regenerative capabilities of infected bone tissue, especially upon the osteogenesis of human bone marrow mesenchymal stem cells (BM-hMSCs). This study evaluates the effects of the three most common fungicides for the systemic treatment of bone infections, Voriconazole (VOR), liposomal Amphotericin B (LAMB), and Fluconazole (FLU), as well as the effects of VOR and LAMB-loaded Polymethylmethacrylate (PMMA) cement chips in different concentrations upon the osteogenic response of BM-hMSCs in vitro. Within this study, we compared the ability of BM-hMSC to differentiate into osteoblast-like cells and synthesize hydroxyapatite as assessed by radioactive 99mTechnetium-Hydroxydiphosphonate (99mTc-HDP) labeling, cell proliferation, and analyses of supernatants upon various osteogenic parameters. Our results revealed that VOR added to the cell culture medium affects the osteogenic potential of BM-hMSC negatively, while there were no detectable effects of LAMB and FLU. Moreover, we showed dose-dependent negative effects of high- and extended-dose fungicide-loaded PMMA cement due to cytotoxicity, with a higher cytotoxic potential of VOR than LAMB, while low-dose fungicide-loaded PMMA had no significant effect on the osteogenic potential of BM-hMSC in vitro.